Optimizing Public Space Quality in High-Density Old Districts of Asian Megacities: Thermal Environment Analysis of Shenzhen’s Urban Fringe - Jie Ren; Xiaohui Xu; Jielong Jiang (Buildings, 2025)
High density old districts at the urban fringes of Asian megacities, such as Shenzhen, face significant thermal challenges due to dense building clusters, limited airflow, and heat retention. This study adopts an integrated approach combining Phoenics wind simulation, geographic information system (GIS) modeling, and spatial prototype analysis to assess and optimize the wind and thermal environments in these urban areas. It investigates how spatial configurations, including building density, height distribution, orientation, and green space integration, influence wind flow and thermal comfort. The results demonstrate that optimized spatial arrangements, including reduced building density, height adjustments, and strategic landscape design, improve ventilation and temperature regulation. Comparative analyses of different spatial prototypes reveal that radial configurations effectively channel external winds into the urban core, enhancing internal airflow, whereas rectangular layouts create wind shadows that hinder ventilation. Adjustments to building façades and vertical arrangements further mitigate pedestrian-level heat accumulation. Interventions in public spaces, including green roofs and vertical greening, offer cooling benefits and mitigate urban heat island effects. This study underscores the importance of aligning urban design with natural wind flow and offers a framework for sustainable landscape and architectural strategies in high-density, heat-prone environments. The findings offer valuable insights for urban planners and policymakers seeking sustainable development in similar megacities.